Analysis of the Notary's Responsibility for Errors in Making a Deed - Darmawan, I Made Yogi; Bagiastra, I Nyoman (West Science Interdisciplinary Studies, 2024)
This research aims to analyze the notary's responsibility for errors in deed preparation, which is a crucial aspect in legal practice in Indonesia. Notaries, as public officials who have the authority to make authentic deeds, play an important role in ensuring the validity of legal transactions. However, errors in making a deed can occur due to various factors, both internal and external, which have the potential to cause legal disputes and financial losses for the parties involved. This research uses a normative method with a qualitative approach to explore the legal norms that regulate the responsibilities of notaries and the implications of errors that may occur. Errors in making a deed can be categorized as typographical errors and substantive errors, each of which has a different impact on the legal force of the deed. Notary responsibilities can be seen from two perspectives, namely civil law and criminal law, depending on the nature of the error that occurred. Research findings show that there is a need to increase awareness of ethics and integrity in notary practice, as well as recommendations for improvements in the implementation of notary duties in order to maintain public trust in this profession. It is hoped that this research can provide a constructive contribution to the development of better notarial practices in Indonesia.